PRODUCTION POTENTIAL OF VEGETATIVE SEED THE MEXICAN SWORD PLANT (Aquarius palifolius (Nees & Mart.) Christenh. & Byng. Family; Alismataceae - Rizki, Rizki; Rasdanelwati, Rasdanelwati; Alfina, Rina; Darlis, Olivia (UNIVERSITAS NEGERI PADANG, 2024)
Vegetative seed production is an alternative for propagating the Mexican Sword Plant, apart from generative propagation using seeds. The vegetative seeds of this plant are unique because they are produced from the development of compound flower stalks (inflorescence). The use of vegetative shoots that appear on the flower stalks of the Mexican Sword Plant is an attractive and efficient alternative in producing seeds for this plant. Apart from that, research on vegetative production is urgent in increasing the production and availability of Mexican Sword Plant seeds. This research was carried out for three months. The study aimed to determine the potential for vegetative seed production of the Mexican Sword Plant-sourced from the shoots of compound flower stalks or inflorescences, which includes the number of main inflorescence axes formed, the number of inflorescence stalks that produce branches, the number of nodes formed on the primary axis inflorescence, the number of buds formed both on the central axis and on the branches of the inflorescence. This research is a descriptive study with observations carried out in the experimental greenhouse of the Politeknik Pertanian Negeri Payakumbuh, Lima Puluh Kota Regency. The parental data was obtained from the results of previous vegetative seed propagation, which was approximately two years old and had been repotted with 30 plants. The media used is a mixture of rice field mud and cow manure using a pot with a diameter of 30 cm. Based on the research that has been carried out, it is known that the central axis of inflorescences formed are 81 inflorescences, 30% each with two inflorescences and 70% with three inflorescences. Five hundred seventy-two nodes (nodes) formed on the central axis, and 488 nodes on the inflorescence branches. The total number of shoots formed was 741, and the average shoots per planting were 25.